PROSEDUR ATAS PERJALANAN DINAS PADA PT TRG INVESTAMA - Eighta Gwyneth, (2022)
The preparation of this final project is as aimed at applying the knowledge that has been obtained during the three years in lectures and developing the insights and knowledge gained. Official travel is an important thing for PT. TRG Investama, because this official trip is closely related to the implementation of its duties. In writing this final project, it aims to get an in-depth overview of the Official Travel Procedures at PT. TRG Investama. In this official travel procedure, it is explained about how the journey or flow from the issuance of a letter of assignment, the process of submitting and disbursing the initial bill to the process of accountability for realization. Based on the discussion of official travel procedures at PT. TRG Investama has been running very well and is effective and efficient.